Pemberdayaan Kelompok Wanita Tani Sitara Kabupaten Jember dalam Membangun Citra Produk Minuman Fungsional: The Empowerment of Sitara Women’s Farmer Group in Jember Regency in Building the Brand Image of Functional Beverage Product - Napitupulu, Tia Sofiani; Nadhirah, Aulia; Sumarlina, Sumarlina; Marseva, Amalia Dwi; Suwandani, Agustina Ni'matur Rahma; Asari, Defan Ari (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The Sitara Women Farmers Group (KWT Sitara) is an enterprise actively engaged in producing bottled functional beverages. In business activities, branding plays a crucial role in enhancing product competitiveness and market value. However, the branding attributes of KWT Sitara’s functional beverages have not yet fully met the required standards, particularly in terms of information completeness, accuracy of elements, and design aesthetics. This community service program aimed to improve the knowledge and skills of KWT Sitara members in developing effective product branding. The methods applied included training sessions, focus group discussions, and hands-on practice in product image design. The results indicated an increase in the participants’ knowledge and skills in building functional beverage product branding. Furthermore, the program produced a finalized design of product branding attributes, consisting of the brand name, product logo, tagline, and product label, all of which were adjusted to comply with applicable regulations.